Financial Sector Assessment : Latvia - World Bank (Washington, DC, 2013)
As part of the joint International Monetary Fund (IMF)-World Bank Financial Sector Assessment Program (FSAP), a joint mission visited Latvia during the period February 14-28, 2001. The principal objective of the mission was to assist the authorities in identifying potential vulnerabilities in the financial system that could have macroeconomic consequences and to identify measures to reduce these risks. The mission also aimed at providing an assessment of the development needs of the financial system and its potential contribution to the economic transformation of Latvia as well as an assessment of the observance of international standards and codes in financial regulation and supervision. The purpose of this Financial Sector Assessment (FSA) report is to provide a summary of the main findings of the February FSAP mission, the policy priorities then identified, and subsequent policy developments that have taken place since.